2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332758
|View full text |Cite
|
Sign up to set email alerts
|

Counted cycles method to quantify the onset response in high-frequency peripheral nerve block

Abstract: The clinical use of high frequency alternating current (HFAC) to block nerve conduction in peripheral nerves is limited due to the large volley of nerve activity generated at the initiation of HFAC. This "onset response" must be characterized in order to determine if it is possible to eliminate it. In this study, preliminary experiments were conducted in an in-vivo animal model using counted cycles of HFAC to investigate and quantify the onset response. Using this method, it is possible to show quantitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…

KHFAC block is generally applied through encircling nerve cuff electrodes and produces a localized block of the underlying nerve [3,16] that does not affect the neuromuscular junction;

KHFAC block is nearly instantaneous, as shown in Figure 2. A recent study [4] used a ‘counted cycles’ method to measure the time to achieve complete motor block and found that it could be as rapid as 7.5–14 ms;

KHFAC block shows rapid reversibility (Figure 2) when the KHFAC is terminated [3]. Experiments demonstrate that the nerve completely recovers within 1 s of the cessation of the KHFAC;
…”
Section: Electrical Nerve Block Using Khfacmentioning
confidence: 99%
See 4 more Smart Citations
“…

KHFAC block is generally applied through encircling nerve cuff electrodes and produces a localized block of the underlying nerve [3,16] that does not affect the neuromuscular junction;

KHFAC block is nearly instantaneous, as shown in Figure 2. A recent study [4] used a ‘counted cycles’ method to measure the time to achieve complete motor block and found that it could be as rapid as 7.5–14 ms;

KHFAC block shows rapid reversibility (Figure 2) when the KHFAC is terminated [3]. Experiments demonstrate that the nerve completely recovers within 1 s of the cessation of the KHFAC;
…”
Section: Electrical Nerve Block Using Khfacmentioning
confidence: 99%
“…A recent study [4] used a ‘counted cycles’ method to measure the time to achieve complete motor block and found that it could be as rapid as 7.5–14 ms;…”
Section: Electrical Nerve Block Using Khfacmentioning
confidence: 99%
See 3 more Smart Citations